Associations Between Neighborhood Characteristics, Social Cohesion, and Perceived Sex Partner Risk among HIV-Seropositive and HIV-Seronegative Women in the Southern United States - Haley, Danielle F. (Arch Sex Behav, 2018)
Neighborhood social and physical factors shape sexual network characteristics in HIV-seronegative adults in the United States. This multilevel analysis evaluated whether these relationships also exist in a predominantly HIV-seropositive cohort of women. This cross-sectional multilevel analysis included dm 734 women enrolled in the Women's Interagency HIV Study's sites in the U S South. Center track-level contextual data captured socioeconomic disadvantage (e.g., tract poverty), number of alcohol outlets, and number of nonprofits in the census tracts where women lived; participant-level data, including perceived neighborhood cohesion, were gathered via survey. We used hierarchical generalized linear models to evaluate relationships between tract characteristics and two outcomes: perceived main sex partner risk level (e.g., partner substance use) and perceived main sex partner non-monogamy. We tested whether these relationships varied by women's HIV. Greater tract-level socioeconomic disadvantage was associated with greater sex partner risk (OR = 1.29, 95 % CI = 1.06-1.58) among HIV-seropositive women and less partner non-monogamy among HIV-seronegative women (OR = 0.69, 95 % CI = 0.51-0.92). Perceived neighborhood trust and cohesion was associated with lower partner risk (OR = 0.83, 95 % CI = 0.69-1.00) for HIV-seropositive and HIV-seronegative women. The tract-level number of alcohol outlets and non-profits were not associated with partner risk characteristics. Neighborhood characteristics are associated with perceived sex partner risk and non-monogamy among women in the South; these relationships vary by HIV status. Future studies should examine causal relationships and explore the pathways through which neighborhoods influence partner selection and risk characteristics.